Metabolic profile of patients with coronary artery disease and comorbid obesity. - T. Maksymets; A. Faynyk; E. Sklyarov (Medičnì Perspektivi)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. Most CVD can be prevented by  modification of such risk factors as tobacco use, obesity and unhealthy diet, physical inactivity and harmful use of alcohol. Patients with CVD or who are at high cardiovascular risk due to the presence of  risk factors such as dyslipidemia, hypertension, diabetes mellitus type 2,  need early detection and management of these states. The article describes differences between metabolic profile of patients with obesity and coronary artery disease. The study included 58 patients. They were divided into 3 groups: 1st - patients with BMI <30 and CAD, 2nd - patients with BMI>30 and CAD, and 3rd - patients with BMI>30. 1st and 2nd group of patients were treated with atorvastatin in the dose of 40 mg for 2 years, 3rd - untreated. The results indicate that significant difference was faund in the lipid profile between groups of patients treated with atorvastatin in the dose of 40 mg . Transaminases and uric acid levels were different but within the reference range. The difference was found in serum glucose, insulin and HOMA-IR between participants of the 2-nd and other groups. We observed significant insulin resistance in the group of patients with coronary heart disease, obesity, treated with atorvastatin. So, administration of atorvastatin to the patients with IHD and obesity may negatively impact carbohydrate exchange and serve as a possible cause of diabetes melitus type 2 development.